Public Private Community Partnership in Ngebel Lake Tourism Development, Ponorogo Regency - Sholikhah, Nikmatus; Tamrin, M. Husni (Universitas Muhammadiyah Sidoarjo, 2023)
Tourism development is one of the priority sectors in a country because the influence of tourism is able to drive economic growth and become the country's largest foreign exchange earner. In developing tourism, the government has entered into partnerships such as that carried out by the Ponorogo Regency Government with the Moroccan International Group Of Development, Technologies And Construction Companies (GDTC) and the Ngebel Tourism Awareness Group (POKDARWIS) as the government's effort to develop Ngebel Lake tourism. The purpose of this research is to describe and analyze the characteristics of the Public, Private, and Community Partnership (PPCP) in the development of tourism in Ngebel Ponorogo Regency as well as the supporting and inhibiting factors. The method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The data analysis technique uses data collection, data reduction, data display and verification. The results of this study found that the partnership between DISBUDPARPORA Ponorogo Regency, GDTC International Morocco and POKDARWIS Ngebel has not gone well, there are still obstacles between the government and private parties and in the budget that was initially submitted by the private party, they switched to using the APBD budget with government problems, which did not immediately make BUMD a requirement for disbursement of funds from the private sector. Therefore, it is necessary to improve the characteristics of successful partnerships so that stakeholders can improve themselves before collaborating